Potensi Ekstrak Daun Jambu Batu (Psidium Guajava) dalam Memperkecil Perombakan Protein Kasar Makanan oleh Mikroba Rumen - Toha Sutardi; S.A. Arianto (Buletin Ilmu Makanan Ternak, 1986)
Formaldehyde is commonly used to minimize ruminal degradation of feed protein to ammonium. Its use however, could cause overprotection. An in vitro trial was designed to compare aquous extracts of Psidium guajava leaves, known to contain tannic acid, with formaldehyde solution in affecting ammoniogenesis, fermentability, anddigestibility. Peanut oil meal containing 34.9% crude protein was subjected to 7treatments: A= untreated, B=5%, C=10%, D=15% (W/V) Psidium leaf extract, E=0.5%, F=1.0%, and G=1.5% (W/V) formaldehyde solution. The treatment were applied prior to the ruminal fermentation at 2 ml/g peanut oil meal.Ammoniogenesis was significantly reduced by the formaldehydeolution to lesser extent also by the leaf extracts (A vs BCD vs EFG=6.21 vs 5.16 vs 3.23 mM ammonia/hr). The 15% leaf extracts, the 1.0% and the 1.5% formaldehyde lowered fermentability of organic matter (Avs D vs FG=18.2 vs 11.6 vs 7.27 mM VFA/hr). Allformaldehyde solution reduce either the dry matter (IVDMD) or the organic matter (IVOMD) digestibility (IVDMD : A=62.1% vs EFG=47.6%). The digestibility wasn't dramatically reduced by the leaf extracttreatments (IVDMD : A=62.1% vs CD=50.1%; IVOMD:A=58.8% vs D=46.2%). The mild effects of psidium leaf extractseventually. lead to more precipitable protein (microbial dietary/origin) (A=10.4% vs BCD =12.1% vs EFG=10.6%, suggesting that the extract has a potential to present more protein to the lower G.I. tract.